ADS660 : Seminar in global affairs / Faculty of Administrative Science & Policy Studies - UiTM, Faculty of Administrative Science & Policy Studies (2023)
This course gives a critical and contextual understanding of the various current international issues. Amongst those covered include the dominant power play in the post-Cold War era, the effectiveness or otherwise of the United Nations as a world body, human rights questions, the impact of globalization, the possible and critical threats to the environment, and the rise of China as a powerful international actor.